2022
DOI: 10.1177/02676591221082499
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hemolysis with centrifugal pumps in pediatric extracorporeal membrane oxygenation: Is pump replacement an answer?

Abstract: Introduction Hemolysis during pediatric extracorporeal membrane oxygenation (ECMO) is associated with increased risk for renal failure and mortality. Objectives We aim to describe risk factors for hemolysis in pediatric ECMO supported by centrifugal pumps. Methods We conducted an analysis of retrospective data collected at an academic children’s hospital from January 2017 to December 2019. Measurements and results Plasma-free hemoglobin (PFH) levels were measured daily, and hemolysis was defined as PFH>50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Numerous studies show the association of elevated PFH with AKI, and other adverse outcomes in patients on ECMO. [1][2][3][4] In addition, Betrus et al showed enhanced hemolysis during combined ECMO and CRRT compared with ECMO alone. 11 In a retrospective analysis of patients requiring ECMO (n = 207, median age 0.13 years), those with severe hemolysis (defined as peak PFH > 100 mg/dL) had greater odds of mortality in the intensive care unit (adjusted odds ratio [aOR]: 5.93; 95% confidence interval [CI]: 1.64-21.43) and hospital (aOR 6.34; 95% CI: 1.71-23.54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies show the association of elevated PFH with AKI, and other adverse outcomes in patients on ECMO. [1][2][3][4] In addition, Betrus et al showed enhanced hemolysis during combined ECMO and CRRT compared with ECMO alone. 11 In a retrospective analysis of patients requiring ECMO (n = 207, median age 0.13 years), those with severe hemolysis (defined as peak PFH > 100 mg/dL) had greater odds of mortality in the intensive care unit (adjusted odds ratio [aOR]: 5.93; 95% confidence interval [CI]: 1.64-21.43) and hospital (aOR 6.34; 95% CI: 1.71-23.54).…”
Section: Discussionmentioning
confidence: 99%
“…Heme pigments can cause direct tubular injury, tubular obstruction, and lead to AKI. Numerous studies show the association of elevated PFH with AKI, and other adverse outcomes in patients on ECMO 1‐4 . In addition, Betrus et al showed enhanced hemolysis during combined ECMO and CRRT compared with ECMO alone 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cutoff of 50 mg/dl for plasma-free hemoglobin was used because this is well established in the ECMO literature. 6,11,14,15 For LDH, 2500 units/L was chosen because there were no values ,600 units/L when LDH was measured, and 2500 units/L was the upper limit of the lowest tertile of results. Hemoglobin and platelet counts were treated as continuous variables.…”
Section: Primary Exposuresmentioning
confidence: 99%